2021
DOI: 10.1039/d0np00086h
|View full text |Cite
|
Sign up to set email alerts
|

Balancing skeleton and functional groups in total syntheses of complex natural products: a case study of tigliane, daphnane and ingenane diterpenoids

Abstract: The fruitful advancement in synthetic chemistry of the title families of complex diterpenes has stimulated and enjoyed strategic balance between building the skeletons and installing the functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 112 publications
0
26
0
Order By: Relevance
“…TMS-dithiane (87) was prepared by treating dithiane (88) with n-butyl lithium (nBuLi) and quenching the resulting anion with trimethylsilyl chloride (TMSCl). Subsequent treatment of TMS-dithiane (87) with nBuLi provided the TMS-dithiane anion (89), which when reacted with epoxide 84, followed by addition of epi-chlorohydrin (86), afforded the desired disubstituted dithiane (90). Interestingly, unmasking the acyl anion equivalent (i.e.…”
Section: Linear Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…TMS-dithiane (87) was prepared by treating dithiane (88) with n-butyl lithium (nBuLi) and quenching the resulting anion with trimethylsilyl chloride (TMSCl). Subsequent treatment of TMS-dithiane (87) with nBuLi provided the TMS-dithiane anion (89), which when reacted with epoxide 84, followed by addition of epi-chlorohydrin (86), afforded the desired disubstituted dithiane (90). Interestingly, unmasking the acyl anion equivalent (i.e.…”
Section: Linear Synthesismentioning
confidence: 99%
“…1), [89] and in turn attracted considerable synthetic attention. [90] Partial Synthesis Partial synthesis (or semi-synthesis) relates to natural product synthesis using a mixture of biosynthetic, degradation, and FGI-inspired retrosynthetic concepts. This often means that the skeleton is already (or mostly) intact and that FGI chemistry is then deployed to achieve the synthesis of the target.…”
Section: Chemical Degradationmentioning
confidence: 99%
“…For instance, picato (ingenol 3-angelate), a protein kinase C activator isolated from E. peplus, has been approved by FDA in 2012 as the first-in-class drug for the treatment of actinic keratosis. 8 Its precursor, ingenol, has been elaborately total synthesized by many research groups, [9][10][11][12] among which Baran and co-workers reported a highly stereocontrolled synthesis in only 14 steps using a two-phase strategy. 11 Euphorbia stracheyi Boiss is a perennial herbaceous plant distributed in some southern provinces of China.…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable biological activities and architecturally complex structures, rhamnofolane, tigliane, and daphnane diterpenoids, have drawn considerable attention from organic chemists. , Numerous laboratories over several decades have together provided many creative strategies for constructing the unique 5/7/6-ring system. To date, the groups of Wender, Cha, Baran, Li, Liu, and Inoue have reported successful total syntheses of these molecules by applying a series of powerful and selective transformations.…”
Section: Introductionmentioning
confidence: 99%